Analisis Penggunaan Makna Denotatif dan Konotatif pada Penulisan Berita Siswa Kelas VII di SMP Negeri 1 Ngrampal Sragen - Agustina, Nova Dwi; , Drs. Andi Haris Prabawa, M.Hum (2017)
Abstract This reseaech aims to describe meaning denotative and meaning connotative manner of students on news. The research in qualitative research. The object of this research I the result of students class VII news. The data research is a student VII SMPN 1 Ngrampal Sragen. Engineering data collection in this research used technique library, roll, and note. Analysis of data for this research in a padan. The result of this research is the first, in a wreath of many tudent found said containing meaning denotative. Meaning denotative that is often used for colloquial and easy to understand. Second in a wreath of students were also found said containing meaning connotative manner. Meaning connotative manner divided into several namely 10 connotation high, because of said containing value high flavor, 2) connotation friendly, deserve enunciated or expressed to interlocutor; 3) connotation dangerous, the word is frequently banned for spoken in a particular situasion; 4) connotation inappropriate, said that should not spoken and having value of inappropriate; 5) connotation bad, a word not you are by the ear, 6) connotation rough, said that have value the rough to pronounce; 7) connotation hard, as the having meaning hyperbole; 8) connotation down, word has meaning down from signification formely; and 9) connotation up, word has meaning up from signification formely. Password : meaning denotative, connotative meaning, connotation